Economic Analysis of Adoption of Improved Rice Varieties by Small Holder Farmers in Manipur - Singh, Kh. Rishikanta; P, Punitha.; Prakash, N. (Indian Journal of Hill Farming, 2018)
The study analyzes adoption of improved rice varieties by resource poor small holder farmers in Manipur state. For the present study six districts viz. Imphal East, Imphal West, Ukhrul, Chandel, Churachandpur and Tamelglong comprising of both valley and hill areas were randomly selected. From these selected districts, a total of 300 paddy cultivating households were randomly selected comprising of 150 adopter farmers and 150 non- adopter farmer. Descriptive statistics, Ordinary Least Square Regression Analysis and Binomial Logit Model were used to analyse the data collected from farmers. Among the adopter’s group, maximum farmers adopted RC Maniphou-10 followed by RC Maniphou-7. Non adopter farmers cultivated local traditional cultivars. It has been found that the average cost of cultivation of rice for adopter group was Rs 46975 / ha as compared to Rs. 43242/ ha for non-adopter. In both the groups, maximum expenditure on cost of cultivation was incurred on human labour comprising more than 50 % of the total expenses. Adopter farmers receive an average net return of Rs. 42341 / ha compared to only Rs. 28502 /ha for non-adopter farmers. The benefit cost ratio was work out to be 1.90 and 1.66 for adopter and non-adopter group respectively. Regression analysis revealed that adopter farmers can increase the yield by using more of fertilizer and plant protection chemicals. Among the various socio economic factors affecting the adoption of improved rice varieties, age has a significant and negative effect while literacy level, family size, yield and number of training programme attended have a positive and significant effect. The study suggested that more emphasis should be given to young and educated farmers for higher adoption of improved rice varieties in the state.